2016
DOI: 10.3390/f7110250
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Anthropogenic Fire Occurrence in the Boreal Forest of China Using Logistic Regression and Random Forests

Abstract: Frequent and intense anthropogenic fires present meaningful challenges to forest management in the boreal forest of China. Understanding the underlying drivers of human-caused fire occurrence is crucial for making effective and scientifically-based forest fire management plans. In this study, we applied logistic regression (LR) and Random Forests (RF) to identify important biophysical and anthropogenic factors that help to explain the likelihood of anthropogenic fires in the Chinese boreal forest. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 48 publications
3
20
0
5
Order By: Relevance
“…ARDL analysis revealed that maximum temperature is the most important variable affecting grassland fires in Xilingol (Table 4), a finding consistent with other studies in northern China and worldwide that show a relationship between higher temperatures and increased fire activity (Kobayashi et al 1994;Su and Liu 2004;Hardy 2005;Kaloudis et al 2005;Zhijun et al 2009;Chen et al 2008). Guo et al (2016) found that as the temperature increased, the amount of boreal forest burned in China increased, even when increased temperatures were accompanied by higher than normal precipitation. Wind and sunlight also explain significant long-term changes in area burned.…”
Section: Discussionsupporting
confidence: 87%
“…ARDL analysis revealed that maximum temperature is the most important variable affecting grassland fires in Xilingol (Table 4), a finding consistent with other studies in northern China and worldwide that show a relationship between higher temperatures and increased fire activity (Kobayashi et al 1994;Su and Liu 2004;Hardy 2005;Kaloudis et al 2005;Zhijun et al 2009;Chen et al 2008). Guo et al (2016) found that as the temperature increased, the amount of boreal forest burned in China increased, even when increased temperatures were accompanied by higher than normal precipitation. Wind and sunlight also explain significant long-term changes in area burned.…”
Section: Discussionsupporting
confidence: 87%
“…Railways reflect a transportation corridor in Yichun, and national fire records reveal that the majority of fire occurrences during this study period were accidental and negligent fires caused by human activities in and around railways, fire accidents by machinery, or lack of controlled burning activities near the tracks and railway infrastructure. Similar negative correlation between distance to railway and fire frequency was reported in the Upper Midwest states and Missouri and boreal forest in China [50][51][52]. On the contrary, Guo et al [53] reported a positive relationship between fire and distance to railway in subtropical forest in China and [3] reported both positive and negative relationships with spatial distribution in the study area.…”
Section: Discussionsupporting
confidence: 78%
“…Nonetheless, various studies [35][36][37][38] have successfully applied the logistic regression approach to evaluate the relationship between factors and fire events. The analysis results in a binary outcome of a fire-event or a non-fire-event.…”
Section: Data Processing-fire Danger Probability Modelmentioning
confidence: 99%